Soluble CD40L is associated with insulin resistance, but not with glucose tolerance in obese nondiabetic patients. (26th May 2016) - Gateva, Antoaneta; Assyov, Yavor; Tsakova, Adelina; Kamenov, Zdravko
Abstract: Objective : The soluble platelet secreted ligand CD40 (sCD40L) has a role in atherosclerosis progression. The aim of the present study was to investigate the link between the levels of sCD40L and some classical cardiovascular risk factors in obese nondiabetic patients. Methods : In the present cross-sectional study, we included76 patients with mean age of 50.7 ± 10.7 years. Oral glucose tolerance test (OGTT) was performed in all participants and levels of sCD40L were measured using enzyme-linked immunosorbent assay (ELISA) method. Results : We found significantly higher levels in patients with insulin resistance compared to those without (6.4 ± 3.7 vs. 4.1 ± 2.4 ng/ml, р  = 0.025) and only a tendency toward higher levels in prediabetes compared to normoglycemic patients (5.9 ± 3.6 vs. 5.3 ± 3.4 ng/ml). There was no correlation between sCD40L and platelet count, systolic and diastolic blood pressure and lipid profile. Conclusions : The main factor for increased sCD40L plasma levels was the presence of insulin resistance and not the state of glucose tolerance.